2005
DOI: 10.1007/s00239-004-0189-2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Differences in Content and Intensity of Periodic Proteins

Abstract: (247 words): Many proteins exhibit sequence periodicity, often correlated with a visible structural periodicity. The statistical significance of such periodicity can be assessed by means of a chi-square-based test, with significance thresholds being calculated from shuffled sequences. Comparison of the complete proteomes of 45 species reveals striking differences in the proportion of periodic proteins and the intensity of the most significant periodicities. Eukaryotes tend to have a higher proportion of period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A survey on internal repeats in protein sequence databases [33] indicated that eukaryotes have a 3-4 fold higher incidence of internal repeats, as compared to prokaryotes or archaea [34]. Furthermore, long proteins often resulted from the concatenation of internal TRs.…”
Section: Discussionmentioning
confidence: 99%
“…A survey on internal repeats in protein sequence databases [33] indicated that eukaryotes have a 3-4 fold higher incidence of internal repeats, as compared to prokaryotes or archaea [34]. Furthermore, long proteins often resulted from the concatenation of internal TRs.…”
Section: Discussionmentioning
confidence: 99%
“…The use of alternative alphabetic representations, i.e., the predefined groups of residues, considerably assists in highlighting periodicities in structural and / or functional properties of proteins that may be obscured in the standard 20-letter alphabet [8,9]. The obtained sets of periodicities at fixed orders of Fourier transform [11,13] therefore represent a body of periodicity profiles where each terminal sequence of secreted proteins (Table 1) has one profile for each predefined group of residues.…”
Section: Discussionmentioning
confidence: 99%
“…Subset B represented: neutral and weakly hydrophobic (A, G, P, S, T), hydrophilic acid (D, E, N, Q), hydrophilic basic (H, K, R), hydrophobic (I, L, M, V) and hydrophobic aromatic (F, W, Y) residues from Dayhoff alternative alphabetic 6-letter representation [9,15] of amino acids (letters C, D, E, F, G, respectively). Cysteine as the remaining separate group (letter A in Dayhoff alphabet) was not considered due to its presence in very few terminal fragments of proteins under study (Table 1).…”
Section: Swiss -Prot/mentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide repeats occurring in protein coding genes can result in protein sequences containing repetitive elements. Though less studied than DNA repeats, peptide repeats are likewise known to be widespread in nature [ 6 - 8 ]. Peptide TRs impart a modular architecture to proteins and are found in important structural proteins such as animal collagens and keratins, insect and spider silks, plant cell wall extensins, and the proteins that form adhesive plaques and byssal threads of bivalve mussels [ 9 - 13 ].…”
Section: Introductionmentioning
confidence: 99%